Social media impact on marital conflict among married couples in three Southwestern Nigerian states - Omokhabi, Abiola Adiat; Omokhabi, Udukhomose Suleiman; Oloyede, Teslim Opeyemi (Center for Sociological Studies and Community Developmen, 2025)
This study examined the influence of social media on marital conflict among married couples in three Southwestern states of Nigeria. A cross-sectional survey research design was adopted for the study. The study population comprised all married couples residing in three local government areas: Ibadan North in Oyo State, Akoko-South West in Ondo State and Ado in Ekiti State. A sample of 345 married couples was selected using convenience and snowball sampling techniques. Self-administered questionnaires: Social Media Use (r=0.85) and Social Media Impact on Marital Conflict (r=0.76) generated by the web-based application were used for data collection and analyzed using one-way analysis of variance. The results indicate that social media networking tools commonly used by married couples are Facebook and WhatsApp, and that social media uses influence marital conflict. In addition, the study revealed that couples aged 40 and above were the primary social media users. There was no significant difference in social media use based on gender, number of children, religion, length of marriage, and educational attainment. Couples should be educated about the potential impact of social media on their relationship. Workshops and information sessions could help couples understand how excessive use or certain interactions on social media can contribute to marital conflict.